A-FABP mediates adaptive thermogenesis by promoting intracellular activation of thyroid hormones in brown adipocytes - Lingling Shu (Nature Portfolio, 2017)
The protein A-FABP is secreted from adipocytes and known to regulate glucose and lipid metabolism. Here the authors show A-FABP enhances thermogenesis by promoting the conversion of thyroxine T4 to the bioactive form, T3, in brown adipocytes, and by enhancing fatty acid uptake of brown fat.